Digitala fotogrammetriska arbetsstationer för skoglig flygbildstolkning - Önneholm, Kristoffer (SLU/Dept. of Forest Resource Management, 2008)
SCA Skog has taken the initiative to this Master's thesis. Today SCA Skog has a great need to update their informtion on young forest stands across large areas. Traditional field inventory methods for updating stand databases are expensive and time consuming. However, the inventory could be made more efficient if stand boundaries and stand characteristics are derived from aerial photographs. The access to digital aerial photographs and the developments in photogrammetry have led to new opportunities for forest organisations to do the photo interpretation needed to update stand databases on their own. The aim of this Master's thesis is to compare different commercially available digital work stations used to interpret aerial photographs and to recommend two alternative systems: one for interpreters that use it daily (Professional system) and one for interpreters that use the system less regularly. A third purpose has been to specify the hardware needed to run different digital work stations. The fourth and last purpose has been to investigate if it is possible to determine the need for thinning cuttings in young forest stands from aerial photographs. The main conclusions are that more advanced workstations are preferable to systems intended for less advanced and less frequent use. To get a complete view of the function of the system, it is important to test that the workstation is fully compatible with the organisations GIS. None of the studied systems are as suitable as the old SOS-map system (which has, until today, been commonly used for photo interpretation by the forest sector in Sweden) for measurements and interpretations in forest applications. If digital stereo photographs are to be used at a district level, the recommendation is that complete projects should be available so the operator can mount the photos for stereo viewing (including orientation of the stereo model) and start the interpretation by "pushing a button". The results from the thinning cutting study show that the interpreters tend to overestimate rather than underestimate the need of thinning cuttings in young stands. How accurately the need for thinning cutting can be assessed depends on the quality of tree height and volume density estimates from the aerial photographs. By combining the data from the photo interpretation with information from existing stand databases (e.g., tree species, site index, and age), it might be possible to improve the quality of the assessment pertaining to the need of thinning cutting. Today, a common method to identify stands needing to be thinned is to select them using the information available in the stand database. Having access to up-to-date digital aerial photographs of high quality will make it possible to further improve the selection of the potential thinning stands. The use of aerial photography also makes it possible to delineate areas within stands that needs to be thinned .